Biohybrids for Environmental Remediation and Biosensing Concept, Synthesis and Future Prospective - Mishra A.; Rastogi A.; Parmar A.S. (My University, 2025)
Biohybrid are multifaceted materials with wide range of applications in the field of material science, environmental clean-up, drug delivery, etc. The concept is to use the available biomaterials like proteins, microorganisms etc., efficiently by associating them with a suitable inorganic material to develop novel biohybrid materials. In biohybrid materials, biomolecules offer functionality while the inorganic component provides stability and thus leads to the development of biohybrids with dual functionality. Biohybrids (a combination of biomolecule with support) offer several advantages over use of only biomaterial as well as a support. Due to their advantageous features, biohybrids are best suited candidates for bioremediation and biosensing of heavy metals and other pollutants. By using a biohybrid as a sorbent, it is even possible to develop continuous systems for bioremediation. In the present chapter, the focus will be on biohybrids, their various components, synthesis of biohybrid materials using different routes and their applications. Further, the future prospective of application of biohybrids in bioremediation and biosensing will be elaborated to enrich their practical applicability. © 2024 Anju Malik and Vinod Kumar Garg.